If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2v + 1) = (5v + 16) Reorder the terms: 3(1 + 2v) = (5v + 16) (1 * 3 + 2v * 3) = (5v + 16) (3 + 6v) = (5v + 16) Reorder the terms: 3 + 6v = (16 + 5v) Remove parenthesis around (16 + 5v) 3 + 6v = 16 + 5v Solving 3 + 6v = 16 + 5v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-5v' to each side of the equation. 3 + 6v + -5v = 16 + 5v + -5v Combine like terms: 6v + -5v = 1v 3 + 1v = 16 + 5v + -5v Combine like terms: 5v + -5v = 0 3 + 1v = 16 + 0 3 + 1v = 16 Add '-3' to each side of the equation. 3 + -3 + 1v = 16 + -3 Combine like terms: 3 + -3 = 0 0 + 1v = 16 + -3 1v = 16 + -3 Combine like terms: 16 + -3 = 13 1v = 13 Divide each side by '1'. v = 13 Simplifying v = 13
| X^2=94x | | 2a+2b=32 | | 5x+47=-6(x+5) | | 2x^3-9x^2-3=0 | | 100[0.03(p+5)]= | | (9x+5)(9x+5)=126 | | 32=-16t^2 | | 3-10x-8x^2=0 | | (2x+-5)(x+1)=2 | | (3a-5)+2a=90 | | 5n-2+3n=10 | | 4X=1100 | | 3x(-2x+8)=-4 | | 4n+3=28 | | 2x+47=-6(x+5) | | 8.4+1.5x=20.8 | | 3x-(x+8)=-4 | | 3.8t+9.92=-9.46 | | 3.8+9.2=-9.46 | | 6x+23=11x+2 | | 5x(x-2)=5x^2+40 | | x^3-3x^2-41=0 | | 19x=3705 | | 3x^2-17=10 | | -25y^2-128y+112=0 | | g-1=7.8 | | 2x^2-56x+392=0 | | 2x^2+56x+392=0 | | 2x+2y+3z=6 | | A=3.14m^2 | | 7+4.50y=2009 | | -8x^2+16x+280=0 |